2009
DOI: 10.1038/mp.2009.91
|View full text |Cite
|
Sign up to set email alerts
|

Stress and IL-1β contribute to the development of depressive-like behavior following peripheral nerve injury

Abstract: The physiological link between neuropathic pain and depression remains unknown despite a high comorbidity between these two disorders. A mouse model of spared nerve injury (SNI) was used to test the hypothesis that nerve injury precipitates depression through the induction of inflammation in the brain, and that prior exposure to stress exacerbates the behavioral and neuroinflammatory consequences of nerve injury. As compared with sham surgery, SNI induced mechanical allodynia, and significantly increased depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
154
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(176 citation statements)
references
References 55 publications
15
154
1
6
Order By: Relevance
“…Although the neurobiological mechanisms underlying the effects of MD on nociceptive responding in adulthood remain unknown, it has been shown that MD induces a range of sex-dependent developmental and psychoneuroimmunendocrine alterations 54 . It has been proposed that Alterations in affective responding such as anxiety-and depressive-like behaviours have been shown to be induced in a number of models of peripheral nerve injury 45,47,51,57 , although in the present study SNL failed to modulate affective behaviour. The short period following surgery over which these behaviours were examined (Day16), may account for the lack of effects as previous studies have indicated that alterations in affective behaviour only manifest after at least a month post-surgery 45,51,57 .…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Although the neurobiological mechanisms underlying the effects of MD on nociceptive responding in adulthood remain unknown, it has been shown that MD induces a range of sex-dependent developmental and psychoneuroimmunendocrine alterations 54 . It has been proposed that Alterations in affective responding such as anxiety-and depressive-like behaviours have been shown to be induced in a number of models of peripheral nerve injury 45,47,51,57 , although in the present study SNL failed to modulate affective behaviour. The short period following surgery over which these behaviours were examined (Day16), may account for the lack of effects as previous studies have indicated that alterations in affective behaviour only manifest after at least a month post-surgery 45,51,57 .…”
Section: Discussioncontrasting
confidence: 53%
“…Moreover, MD females also exhibited enhanced mechanical (ipsilateral) and cold (bilateral) allodynia 14 days following SNL compared with control females. Mechanical allodynia following peripheral-nerve injury has been shown to be enhanced following chronic restraint stress and in a genetic model of depression (Wistar-Kyoto rat) 47,58 , however, to our knowledge, this is the first study to examine the effect of early-life stress on neuropathic pain behaviour in rodents. Although the neurobiological mechanisms underlying the effects of MD on nociceptive responding in adulthood remain unknown, it has been shown that MD induces a range of sex-dependent developmental and psychoneuroimmunendocrine alterations 54 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a further study, chronic restraint stress-induced hyperalgesia was associated with reduced expression of the glial fibrillary acidic protein (GFAP), an astrocyte biomarker, and the excitatory amino acid transporter 2 (EAAT-2) in the PAG (Imbe et al, 2012)). Furthermore, hyperalgesia observed in a mouse model of spared nerve injury following exposure to restraint stress, was associated with increased the mRNA expression of GFAP, BDNF and interleukin (IL)-1 in the PAG (Norman et al, 2010).…”
Section: Periaqueductal Grey (Pag)mentioning
confidence: 99%
“…Pre-clinical studies have demonstrated peripheral nerve injury-induced neuroimmune activation in brain regions responsible for the modulation of nociception and/or affect, including the prefrontal cortex (Apkarian et al, 2006, Al-Amin et al, 2011. Furthermore, the expression of genes coding for the pro-inflammatory cytokines IL-1β, IL-6 and/or TNFα, is enhanced in brain regions responsible for processing emotion and pain in animal models of depression with concomitant inflammatory (Kim et al, 2012, Arora et al, 2011 and neuropathic (Norman et al, 2010, Apkarian et al, 2006, Burke et al, 2013a, Burke et al, 2013b pain-related responding. Thus, modulating neuroimmune responses has been proposed as a novel target for the treatment of CNS disorders with an inflammatory component, including depression and associated chronic pain.…”
Section: Introductionmentioning
confidence: 99%